Eficiencia relativa en el gasto de los gobiernos regionales: un aporte al proceso de descentralización - Ciquero Ibañez, Victor Raúl (2007)
If we consider welfare as a multidimensional phenomenon, we can show that the traditional approach, based on objective indicators and economic determinants, is insufficient. Apart from the positive but imperfect correlation between the household monetary income and subjective welfare, other factors influence that perception. We use the Economic Ladder Question (ELQ) in the Peruvian household surveys to analyze the factors determining economic welfare, employing an ordered logit model. Our research puts emphasis on those factors affected by policy. We show that more than 70% of the population considers itself 'poor' in subjective terms, while according to the poverty line approach, the proportion is 44,6%. This mismatch between subjective and objective measures means that, in urban and rural areas respectively, 53% and 81% of objective non-poor households subjectively consider themselves to be poor. Using the ELQ we were able to identify factors in determining subjective economic welfare that have been absent in previous research, including: (1) feelings of inclusion in the political and economic system; (2) participation in institutions with decision-making power; (3) the urban poverty characteristics of Lima; and (4) the importance of the reference group in welfare evaluation. The paper concludes by recommending specific policies that focus on the determinants of subjective welfare and by suggesting the importance of using the ELQ to improve the design and evaluation of public policy within a social management framework.